Innovative in teaching Mandarin through scaffolding strategies / Yann Sheng Chan ... [et al.] - Yann, Sheng Chan; Choo, Peng Tan; Oi, Leng Chong; Chun, Keat Yeap (2021)
The arrival of advanced communication and information technologies has changed the method of teaching and learning in the 21st century. Thus, different types of impactful teaching approaches have been applied by educators to ensure that the focus of education is not only to deliver knowledge but also to cultivate students' problem solving, creativity, collaboration and communication skills. In view of a subject which is totally new to students, they need time to learn and practise the skills learned which include listening, speaking, reading and writing. However, the credit hour for the particular subject is only two hours per week, which is a challenge for the lecturer to guide students in achieving the learning outcomes of the subject and to implement the teaching and learning process. Therefore, the scaffolding teaching method was chosen as an action research to see the impact on student's learning. The focus of the study was Introductory Mandarin Level 1. The new roles of teachers were applied through a mechanism including self-learning, group discussion, and presentation. Lecturer had designed and created self-learning notes as a reference to help students understand the particular lesson, facilitated students using effective questioning skills and summarized the lesson at the end to scaffold students' learning. At the end of the semester, students were required to answer a survey questionnaire regarding teaching and learning. This approach gave a positive result which showed that it managed to motivate students to participate in class. Students enjoyed the activities in class and were more active and confident to express their ideas as they understood the topic well during their discussion rather than one way lecture in the class.